Reflections on the Innovation of University Education and Technology under the Background of COVID-19 Epidemic - Yajing, Gao (International Journal of Management and Education in Human Development, 2022)
A sudden outbreak at the end of 2019 caught us unawares and without time to deal with it, and all industries were hit hard and are still not completely gone, but the response of the education sector was the most timely and logical in the response to the New Coronavirus. This paper is an in-depth reflection on innovation in university education and technology in the context of the New Coronavirus epidemic. While illuminating the impact and influence of the New Coronavirus epidemic on universities, it also provides insight into the future of university education reform, thus helping universities to develop in the long run.